Recent advances in the understanding of Xanthomonas citri ssp. citri pathogenesis and citrus canker disease management - Ference, Christopher M.; Gochez, Alberto Martin; Behlau, Franklin; Wang, Nian; Graham, James H.; Jones, Jeffrey B. (2018)
Taxonomic status: Bacteria; Phylum Proteobacteria; Class Gammaproteobacteria; Order Xanthomonadales; Family Xanthomonadaceae; Genus Xanthomonas; Species Xanthomonas citri ssp. citri (Xcc). Host range: Compatible hosts vary in their susceptibility to citrus canker (CC), with grapefruit, lime and lemon being the most susceptible, sweet orange being moderately susceptible, and kumquat and calamondin being amongst the least susceptible. Microbiological properties: Xcc is a rod-shaped (1.5–2.0 X 0.5–0.75 mm), Gram-negative, aerobic bacterium with a single polar flagellum. The bacterium forms yellow colonies on culture media as a result of the production of xanthomonadin. Distribution: Present in South America, the British Virgin Islands, Africa, the Middle East, India, Asia and the South Pacific islands. Localized incidence in the USA, Argentina, Brazil, Bolivia, Uruguay, Senegal, Mali, Burkina Faso, Tanzania, Iran, Saudi Arabia, Yemen and Bangladesh. Widespread throughout Paraguay, Comoros, China, Japan, Malaysia and Vietnam. Eradicated from South Africa, Australia and New Zealand. Absent from Europe.